If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -6y + 7x + -1y + -2x + 4x = 0 Reorder the terms: 8x + 7x + -2x + 4x + -6y + -1y = 0 Combine like terms: 8x + 7x = 15x 15x + -2x + 4x + -6y + -1y = 0 Combine like terms: 15x + -2x = 13x 13x + 4x + -6y + -1y = 0 Combine like terms: 13x + 4x = 17x 17x + -6y + -1y = 0 Combine like terms: -6y + -1y = -7y 17x + -7y = 0 Solving 17x + -7y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7y' to each side of the equation. 17x + -7y + 7y = 0 + 7y Combine like terms: -7y + 7y = 0 17x + 0 = 0 + 7y 17x = 0 + 7y Remove the zero: 17x = 7y Divide each side by '17'. x = 0.4117647059y Simplifying x = 0.4117647059y
| 5x+20+90=180 | | x+2x+15=5x+5 | | Y^2+xy-x^2=11 | | -6r=-8r-8 | | 11-15n+4n=-10-4n | | 4x-8sqrt(x)=0 | | 3x-14+2x+25=180 | | 16x+40+(-21x)= | | log(3x+5)=2 | | 8m+2m=10m | | -2(6a+7)=-86 | | log(x+4)=1.3 | | 7+3x=-4w | | 3x-22=80+x | | 8(8+6)-3(8+3(8))=-3(8)-8 | | -7+9y=-6+9y | | 4x-8+1=13 | | 3x+36=7x+12 | | 14x^2+31x+15=0 | | 7p-4-10p=-3p-4 | | -5(-2x+7)= | | q=44 | | 8(b+6)-3(8+3b)=-3b-b | | -9r=-9r+4 | | 8p=-12-3p | | 52x-3+4x=7-44x | | 0=-x+x | | Abs(x-5)=-10 | | -1+9z=6z-10 | | 0=x-x-x | | 6h+9=75 | | 8x-5=48 |